FAKTOR-FAKTOR YANG MEMPENGARUHI PENETAPAN FEE AUDIT EKSTERNAL PADA PERUSAHAAN YANG TERDAFTAR DI BEI - Rizki Nugrahani, Nadia; Sabeni, Arifin (Diponegoro Journal of Accounting, 2013)
This study aims to analyze factors that influence the determination of external audit fees on all companies listed on Bursa Efek Indonesia (BEI). The factors tested in this study are internal audit, corporate governance, the characteristics of auditors (BIG4), firm size, and subsidiaries. Collecting data is using purposive sampling method to all companies listed in Bursa Efek Indonesia (BEI) during 2009-2011. A total of 65 companies in used as sample in this research. This study uses multiple linear regression as the analysis instrument. Before being conducted the regression test, it is examined by using the classical assumption tests.The results of this research showed that the size of the board commissioner, the size of the audit committee, characteristics of the auditor (BIG4), firm size and subsidiaries have significant relationship on the external audit fees. However, internal audit, the independence of the board commissioner, the meeting intensity of the board commissioner, independency of the audit committee, and the meeting intensity of the audit committee did not have significant influence with external audit fees.